Detailed analysis of the transverse arch of hallux valgus feet with and without pain using weightbearing ultrasound imaging and precise force sensors - Zeidan, Hala (PLoS One, 2020)
BACKGROUND: Hallux valgus is the most common forefoot deformity and affects the transverse arch structure and its force loading patterns. This study aims to clarify the differences in the transverse arch structure and the force under the metatarsal heads individually, between normal feet and hallux valgus feet, and between hallux valgus feet with pain and without pain. We further test the association between the parameters of the transverse arch and hallux valgus angle and between the parameters and pain in hallux valgus. METHODS: Women’s feet (105 feet) were divided into normal group (NORM) and hallux valgus group (HVG); and further into subgroups: hallux valgus without pain (HV Pain (-)) and hallux valgus with pain (HV Pain (+)). Transverse arch height and metatarsal heads height were measured using weight-bearing ultrasound imaging. Force under the metatarsal heads was measured using force sensors attached directly on the skin surface of the metatarsal heads. The measurements were taken in three loading positions: sitting, quiet standing and 90% weight shift on the tested foot. Differences between the groups were compared using Student t-test and Wilcoxon Exact test. Multivariate logistic analysis with adjustment for physical characteristics was also conducted. RESULTS: Transverse arch height was significantly higher in HVG than in NORM in all positions; there were no significant differences between HV Pain (+) and HV pain (-). Lateral sesamoid was significantly higher in HVG and HV Pain (+) than in NORM and HV Pain (-) respectively when bearing 90% of the body weight unilaterally. There was a trend of higher forces under the medial forefoot without significant difference. Transverse arch height and lateral sesamoid height were associated with the hallux valgus angle, while lateral sesamoid height was associated with forefoot pain in hallux valgus deformity. CONCLUSIONS: This study shows the differences in the transverse arch structure between normal feet and feet with hallux valgus, and between hallux valgus feet with and without pain. This finding is noteworthy when considering future treatments of painful feet, notably the height of the lateral sesamoid which seems to play a role in forefoot pain.